Urgensi Pengaturan Honorarium Notaris Untuk Kewenangan Selain Membuat Akta Autentik - Farizal, Muhammad; Madjid, Abdul; Kawuryan, Endang Sri (Universitas Negeri Malang, 2022)
This study discussed the urgency of notary honorarium arrangements and reconstruction of notary honorarium arrangements besides making an authentic deed. The study utilized normative juridical research with a statutory approach and a conceptual approach with grammatical interpretation analysis. The urgency of determining the notary's honorarium was related to the philosophical, juridical, economic and sociological urgency. Giving an honorarium to a notary in addition to his authority in an authentic deed was very necessary because it provided legal protection for the rights that a notary should receive for the services that had been provided. The determination of the honorarium aimed to provide legal protection and legal certainty to notaries.